Efficacy of COVID-19 control measures on post-vaccination outbreak in Italian Long Term Care Facilities: implications for policies - Malara, Alba; Noale, Marianna; Trevisan, Caterina; Abbatecola, Angela Marie; Borselli, Gilda; Cafariello, Carmine; Gareri, Pietro; Fumagalli, Stefano; Mossello, Enrico; Volpato, Stefano; Monzani, Fabio; Coin, Alessandra; et al. (Frontiers in Public Health, 2023)
Background Numerous individual and organizational factors can influence the spread of SARS-CoV-2 infection in Long Term Care Facilities (LTCFs). A range of outbreak control measures are still implemented in most facilities involving administrations, staff, residents and their families. This study aims to evaluate which measure could influence the transmission of SARS-CoV-2 infection among residents during the period March 2021-June 2022. Methods We enrolled 3,272 residents aged ≥60 years. The outbreak control measures adopted to prevent or manage the infection included entry regulations, contact-regulating procedures, and virological surveillance of residents and staff. The association between LTCFs' and participants' characteristics with new cases of COVID-19 infections was analyzed using multilevel logistic regression models. Results In 33.8% of the facilities 261 cases of SARS-CoV-2 infection were reported. Among participant characteristics, gender and age were not associated with SARS-CoV-2 infection, while having received the vaccine booster dose was protective against infection [Odds Ratio (OR) = 0.34, 95% Confidence Interval (CI) 0.12–0.99, p = 0.048]. In addition, the implementation of protected areas for family visits was associated with a significant reduction of the probability of infections (OR = 0.18, 95% CI 0.03–0.98, p = 0.047). Overall, about 66% of the variability in the probability of SARS-CoV-2 infection during the observational period may be due to facility structure characteristics and 34% to the participant characteristics. Conclusions These data showed that vaccination booster doses and family visit restriction-control are still needed to make the LTCFs safer against SARS-CoV-2 infection.